Manajemen Krisis Public Relations PT. CFD Traveller Sukabumi dalam Menghadapi Kasus Penipuan Tahun 2024 - Dean Sakti Pratama; Siska Yuningsih (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The fraud case that struck PT CFD Traveller Sukabumi shook the company’s reputation and threatened its relationship with customers, triggering a crisis. This study aims to examine the crisis management of Public Relations at PT CFD Traveller Sukabumi in dealing with the 2024 fraud case, as well as to identify its opportunities and challenges. The research employed a qualitative approach with a descriptive analysis method. Data were collected through in-depth interviews with key informants and individuals directly involved in crisis management. The study applied Coombs and Holladay’s theory, identifying the stages of pre-crisis, crisis, and post-crisis. At the pre-crisis stage, the company conducted risk analysis and careful planning, including communication procedures and employee training. At the crisis stage, the company implemented the plan quickly and in a coordinated manner through clear and open communication with the public and by maintaining good relations with the media to ensure accurate information. At the post-crisis stage, the company carried out comprehensive evaluations, updated its crisis management plan, engaged consumers in the recovery process, and launched campaigns emphasizing customer safety and satisfaction. The findings highlight that structured crisis communication strategies play a crucial role in maintaining public trust.